Amphiphilic Y shaped miktoarm star copolymer for anticancer hydrophobic and hydrophilic drugs codelivery: Synthesis, characterization, in vitro, and in vivo biocompatibility study. Issue 11 (27th August 2018) - Aghajanzadeh, Mozhgan; Zamani, Mostafa; Rashidzadeh, Hamid; Rostamizadeh, Kobra; Sharafi, Ali; Danafar, Hossein
Abstract: In this project, a core‐shell polymersome based on miktoarm star‐copolymer:methoxy poly‐ethylene glycol‐lysine‐(poly‐caprolactone)2 was synthesized by a new method as controlled targeted drug delivery systems for codelivery of the chemotherapeutic methotrexate (MTX) and curcumin (CUR). Some properties of these nanocarriers (NCs), such as surface morphology, structure, surface charge, stability, and biocompatibility, were evaluated by proton nuclear magnetic resonance, dynamic scanning colorimetry, Fourier‐transform infrared spectroscopy, dynamic light scattering, atomic force microscopy, critical aggregation concentration, hemolysis test, MTT assay, and lethal dose 50 (LD50). The AFM results showed that the uniform spherical morphology of NCs have an average size of about ∼60 nm. The drug loading of NCs was about 14.13 and 10.93% for CUR and MTX, respectively. The NCs revealed pH‐sensitivity in drug release. The release of drugs from miktoarm‐based NCs in neutral pH was lower than in acidic medium because of faster degradation of polymersome in acidic environment. MTT assay results showed that the drug‐loaded NCs did not show significant toxicity due to which cell viability maintain over 82% at 300 μg/mL concentration. Also, synthesized miktoarm showed hemolysis lower than 3%. This result was repeated in LD50, and all mice which treat with 5000 mg/kg were still alive after 24 h. These result confirmed safety of miktoarm star copolymer. Eventually, the goal of this study is the application of water‐soluble star copolymers miktoarm with pH dependent release properties for designing a new drug delivery carrier and using CUR for enhancing anticancer properties of MTX. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 2817–2826, 2018.